Steady flow of burgers’ nanofluids over a permeable stretching/shrinking surface with heat source/sink - Yahaya, Rusya Iryanti; Md Arifin, Norihan; Pop, Ioan; Md Ali, Fadzilah; Mohamed Isa, Siti Suzilliana Putri (Multidisciplinary Digital Publishing Institute, 2022)
An engineered fluid, called nanofluid, is expected to have better thermal conductivity than conventional working fluids. The superior heat transfer performance and various possible applications promote the analysis of nanofluids in different flow geometries. This paper studies the flow of non-Newtonian Burgers’ nanofluids over a permeable stretching/shrinking surface with a heat source/sink. In the current study, we highlight the use of the single-phase nanofluid model in studying the boundary layer flow. The basic partial differential equations are transformed into ordinary (similarity) differential equations. Then, the resulting equations and boundary conditions are solved numerically in MATLAB using the bvp4c package. Triple solutions are presented, and stability analysis certifies that the first solution is physically realizable in practice. It is found that the increment of the heat source parameter raised the temperature profile of the nanofluids. Al2O3/H2O and Cu/H2O nanofluids produced the highest skin friction coefficient in the flow over stretching and shrinking surfaces, respectively. Meanwhile, Cu/H2O nanofluid showed a better heat transfer performance when compared to Al2O3/H2O and TiO2/H2O nanofluids. The present study is novel and could serve as a reference to other researchers for further analysis of heat transfer performance and the rheological behavior of nanofluids.